Analisis Pembelajaran Ulumul Qur’an Berparadigma Integrasi Interkoneksi Terhadap Mahasiswa Pendidikan Biologi Universitas Islam Sunan Kalijaga Yogyakarta - Neni Zakiyah; Mahmud Arif (Raudhah - Proud To Be Professional, 2023)
Known as the concept of scientific integration in the form of integration, interconnection, and scientific cobwebs. UIN Sunan Kalijaga Yogyakarta, also has extraordinary appeal in the eyes of Indonesian students. Regarding what makes it special and how the learning process is carried out there, at this time it is still a question that wants to know the answer for those who have never studied there. This study will reveal and analyze how the process of analyzing student learning uses the integration-interconnection paradigm. The good news is that readers don't need to go into the field directly, because just reading this article is enough to know the learning process that takes place on this campus. In this case, the researcher went directly to the field in the Biology Education Study Program by raising the Ulumul Qur'an study as a course to be presented to see the process of learning itself. Next, the researcher will describe the research results based on data collection techniques in the form of observation, classification, and interview results. This research shows that the student learning process will lead to the application of the active learning concept of student-centered learning (SCL) in the learning process at the tertiary level with the types of problem-based learning (PBL), discovery learning, self-directed learning, and contextual learning.